Tantangan dan Peluang dalam Mengadopsi Model Sekolah Penggerak Melalui Pendekatan Progresivisme di SDN Sukatani – Cianjur - Handayani, Sri; Muchtar, Hendi S.; Soleh, Wiwi Sulastri; Yusup, Asep Roby Maulana; Anwar, Anwar (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2024)
Abstract: The School Mover is a transformation in education aiming for institutions to produce student learning outcomes, including literacy and numeracy competencies, along with assessing students' character. It emphasizes transforming schools into the schools mover rather than focusing on popularity, size, or facilities. Sukatani Elementary School in Cianjur Regency is one such school focused on in our research titled